2022
DOI: 10.3390/children9071095
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Coordination Disorder and Most Prevalent Comorbidities: A Narrative Review

Abstract: This narrative review describes, in detail, the relationships between Developmental Coordination Disorder (DCD) and most prevalent associated comorbidities in their complexity, heterogeneity and multifactoriality. The research has been conducted on the main scientific databases, excluding single case papers. Blurred borders between the different nosographic entities have been described and advances in this field have been highlighted. In this multifaceted framework a specific profiling for co-occurring DCD, AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 89 publications
0
12
0
1
Order By: Relevance
“…This study also included children with dual diagnoses; therefore, further studies examining children with a sole diagnosis of DCD may be beneficial. However, it is important to note that DCD is commonly associated with other neurodevelopmental disorders (Lino and Chieffo, 2022). Despite these limitations, the findings suggest that further studies with more diverse services, addressing different needs and using other technologies, are needed.…”
Section: Discussionmentioning
confidence: 99%
“…This study also included children with dual diagnoses; therefore, further studies examining children with a sole diagnosis of DCD may be beneficial. However, it is important to note that DCD is commonly associated with other neurodevelopmental disorders (Lino and Chieffo, 2022). Despite these limitations, the findings suggest that further studies with more diverse services, addressing different needs and using other technologies, are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, given the robust literature examining the relation between ADHD and school functioning, the findings that fine and gross motor competence uniquely predict academic performance above ADHD-risk status have important clinical implications. Beyond experiencing high comorbidity rates with language disorders, dyslexia, and dysgraphia, children with DCD often experience decreased self-esteem, show reduced participation in play groups, and demonstrate higher levels of emotional disorders (Lino & Chieffo, 2022). Therefore, for children experiencing academic impairment, it could be beneficial to examine motor competence in addition to other typical assessments for learning or psychological disorders to gain a more comprehensive view of the child’s functioning.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that neurodevelopmental disorders, such as specific learning disorder (SLD), developmental coordination disorder (DCD), and attention deficit hyperactivity disorder (ADHD) co-occur frequently [ 1 ]. Specific learning disorder (SLD) is considered by the DSM-5 [ 2 ] and is a clinical neurodevelopmental disorder that hinders a child’s ability to learn or use specific academic skills.…”
Section: Introductionmentioning
confidence: 99%
“…Emerging evidence suggests that apart from poor academic functioning, many children with SLD also have motor problems [ 4 , 5 ]. Learning disorders affect 2–10 percent of the school-age population worldwide [ 1 ]. Importantly, among children who present with SLD, there is frequent co-occurrence of other neurodevelopmental disorders such as developmental coordination disorder (DCD) [ 6 ] and attention deficit hyperactivity disorder (ADHD) [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation